The Practice of Da’wah Communication by Muslim Preachers Toward Orang Asli in Klang Valley - Abu Sofi Bin Hasbullah
Da’wah to Orang Asli is not something new for preachers in Malaysia. Various methods are used to ensure that Islamic teachings reach the Orang Asli. There are various barriers faced by the preacher such as the difficulty in mastering the Orang Asli language and the weaknesses shown by the preacher himself. This research was carried out to identify da’wah communication used by the preacher towards Orang Asli to identify barriers of communication preaching faced by the preacher when preaching to Orang Asli and to identify the preparation of the preacher before doing da'wah to Orang Asli. The researcher uses the qualitative method as the research design. Data were obtained through semi-structured interviews involving a total of nine Penggerak Masyarakat Orang Asli (PMOA) in the State of Selangor as study participants. Data were organized and coded according to themes and analyzed descriptively. The results of the study show that Penggerak Masyarakat Orang Asli (PMOA) has various ways to preach to the Orang Asli and most of them like to use the da'wah bill of things when preaching to the Orang Asli such as visiting the Orang Asli home and helping the Orang Asli who are in difficulty. In addition, there are also barriers faced by the preachers such as being bewitched by Orang Asli when preaching and Orang Asli using their houses as churches to spread Christianity to the villagers. Apart from the problems of Orang Asli, there are also problems caused by the Malays such as drinking alcohol and getting drunk with the children of the natives, resulting in a bad perception of the preachers.